Development of IOS apps for circuit modeling and analysis - Li, Wentai (Nanyang Technological University, 2023)
The convenience of using Electronic Design Automation (EDA) tools in the electronic design process is widely acknowledged. However, these tools present a challenge when it comes to quickly determining the parameter matrix of a MOSFET, particularly for students or users looking for a rapid solution. This dissertation addresses this issue by introducing an iOS application designed to calculate the scattering parameters of a MOSFET. This application aims to simplify the process, allowing for rapid computation and providing a conve- nient tool for circuit analysis and design, especially for students and similar user groups. The software has the functionality to compute the scattering pa- rameters of MOSFET based on user-input parameters and display the calculation process. Users have the flexibility to directly view the results or delve into the detailed steps according to their preferences. This provides a convenient means for users to analyze and design circuits. Finally, we conducted auxiliary tests on the software using MATLAB and ADS. The test results indicate that the software has successfully achieved its goal of computing parameters and performs excellently in terms of teaching and rapid calculations.